ENGLISH PHONOLOGICAL PROBLEMS ENCOUNTERED BY BUGINESE LEARNERS - Gusri, Ali Emiyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
One of the language components is phonology. Â Hyman (1975) states that phonology studies the sound system of language. A sound is considered very important in all languages because the language can be understood by listening to its sound. When a speaker of a language makes error in pronouncing the sounds of a word, the meaning of the word can be changed, and then there can be a misunderstanding between the speaker and the listener. By seeing this importance of sounds, one is expected to pronounce the sounds of a word correctly. But, pronouncing the certain sounds of a language is still difficult for some people, mainly the people who learn a new language, including Buginese learners who learn English as a foreign language. One cause of second language learnersâ difficulty inÂ  pronoumcing the target language is the difference between the first language and Â thge target language target system. Some English sounds are different from Buginese sounds, and some English sounds are absent in Buginese language. The aim of this paper is to present some of the difficulties The Buginese learners usually face in learning English pronunciation.